Halaqoh Method to Enhance the Quality of Al Qur’an Learning towards New Students in Islamic Boarding School - Syahrul, Muhamad; Wahyuni, Linna Endah Nur (Anjasmoro: Islamic Interdisciplinary Journal, 2025)
The main problems covered in this study are 1) How is the implementation of the Qur'an education halaqah in the Mansyaul Huda 02 Senori-Tuban Islamic boarding school? 2) How is the quality of Qur'an learning for new students in the Mansyaul Huda 02 Senori-Tuban Islamic boarding school? 3) What is the role of the Qur'an education halaqah strategy in improving the quality of Qur'an learning for new students in the Mansyaul Huda 02 Islamic boarding school. The research method used is a qualitative method with qualitative data collection techniques through observation, interview, and documentation. The data Analysis Techniques are through data reduction, data presentation, and data verification. The results of the study show that the halaqah applied in the Mansyaul Huda 02 Senori Islamic boarding school in everyday life has an important role in improving the Qur'an reading skills of students, such as reading skills. In addition, the halaqah strategy also forms the Islamic character of students by increasing awareness and practice of Islamic values in the daily lives of students in Islamic boarding schools. This study also shows that the halaqah strategy can increase students' motivation and self-confidence, as well as increase students' insight, thereby opening up wider opportunities for the future of students as provisions for living in society and interacting with the global world. This research implies that the halaqah strategy can be one of the effective strategies to form knowledgeable students, have good morals and have good reading of the Qur'an and have broad insight to face future challenges and contribute to society.